(untitled) (Journal of Economic Research & Business Administration, 2022)
The article is devoted to the study of the problems of state tax management in the Republic of Kazakhstan. The initial condition is the absence of uniform methodological and methodical approaches to the formation and organization of tax management, including in conditions of extreme economic instability. The main research methods used were: analysis and synthesis, systemic and institutional approaches, methods of induction and deduction, the method of designing hypotheses. The directions of modernization of the tax regulation system, the impact of mechanisms, methods and tools of tax management on various segments of the national economy, primarily on the industries that ensure economic growth, have been investigated. In order to improve the efficiency of fiscal regulation, a scenario modeling is proposed, which makes it possible to assess the effect of the implementation of various situations on fiscal revenues and key macroeconomic indicators. The result of the study is the development of directions, measures of economic, administrative, financial, political development of the modern level of tax management based on the analysis of the current state of the national tax system, scenario modeling, as well as the empirical design of the strategic SWOT analysis matrix. The theoretical and practical significance of the study lies in substantiating the need for adaptive tax regulation and tax management in order to ensure sustainable growth of the national economy. Key words: tax regulation, crisis, tax system, sustainable economic growth, scenario modeling.